ANALISA PERUBAHAN ORGANISASI MENGGUNAKAN PENDEKATAN ORGANIZATIONAL CHANGE CAPACITY - Manik Pupunden (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Higher education as a form of the organizations is required to remain competitive and adaptive to environmental changes. Responding to this, PTS X made organizational changes by amending the statutes. The Organizational Change Capacity is used to diagnose the accuracy of the steps of organizational change that occurs, and as an instrument for assessing the capacity of organizations to make changes. Quantitative method is used, and the results showed that the highest change capacity is in trustworthy leadership (31.16) and lowest in the cultural dimension of innovation (28.68). The changes made today by PTS. X for organizational structure and governance changes, has not reached the innovative culture dimension, which has the lowest value of the eight dimensions of Organizational change capacity.